Vein Grafts in Free Flap Reconstruction: Review of Indications and Institutional Pearls. Issue 3 (March 2022) - Langdell, Hannah C.; Shammas, Ronnie L.; Atia, Andrew; Chang, Edward I.; Matros, Evan; Phillips, Brett T.
Abstract : Summary: Vein grafts enable soft-tissue reconstruction in cases of insufficient pedicle length, a lack of nearby recipient vessels, and a wide zone of injury caused by trauma or radiation therapy. The purpose of this article is to provide a comprehensive review of vein grafts in free flap reconstruction focusing on the timing of arteriovenous loops, complications, and surgical technique. Vein graft indications, types of vein grafts, and location-specific considerations are also reviewed. Three reconstructive microsurgeons at high-volume centers were asked to offer institutional pearls on the order of anastomosis, selection of donor veins, and timing of arteriovenous loops. In terms of gap length, vessel gaps less than 10 cm may be reconstructed with an interposition or transposition vein graft. For longer gaps, surgeons should consider the use of arteriovenous loops, transposition arteriovenous loops, or flow-through flaps. Both one and two-stage arteriovenous loops are used, depending on patient comorbidities, potential exposure of critical structures, and surgeon preference. Although one-stage arteriovenous loops expedite the reconstructive process, two-stage arteriovenous loops require shorter operations and help identify patients at risk of flap failure. Although whether the use of vein grafts increases flap failure rates is controversial, complications are highest in lower extremity reconstruction, cases of a prolonged interval between stages in two-stage arteriovenous loops, and unplanned vein grafts.